Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have to prove that $1, (1-t), (1-t)^2$, and $(1-t)^3$ is a basis of for $P^{3}$ but I am not sure how to start this problem.

Also I have to find the coordinates of $p(t) = 1 +t^3$

Thank you for the help

share|cite|improve this question
This is a simple variant of the previous problem you posted. Study the solutions there and solve this one analogously. – Lepidopterist Mar 17 '13 at 22:20

You need to show that they span and that they are linearly independent. I would start by showing linear independence. Start with $$a + b(1-t) + c(1-t)^2 + d(1-y)^3 = 0.$$ Then by expanding and comparing coefficients prove that $d = c = b = a = 0$.

Now if you know something about dimension then you're done, because the dimension of $P_3$ is $4$. If not, then you'll have to show that the basis spans, so you'll have to show, given $$f = a + bt + ct^2 + d^3,$$ how to express $f$ as a linear combination of the basis. This is a little messy to write out, but shouldn't be hard.

share|cite|improve this answer

The first question follows directly from the change of variable $u = 1-t$.

The same idea can be used for the second question: $$ 1+t^3 = 1 + (1-u)^3 = 1 + (1-3u+3u^2 - u^3) = 2 - 3u + 3u^2 - u^3 $$

share|cite|improve this answer

The operator $\phi:P^3\longrightarrow P^3$ defined by $\phi(P)(t)=P(t-1)$ is an isomorphism of inverse given by $\phi^{-1}(Q)(t)=Q(t+1)$. Therefore, it takes very basis onto a basis. Starting with the canonical basis $\{p_0(t)=1, p_1(t)=t, p_2(t)=t^2, p_3(t)=t^3\}$, we obtain the basis $$\{\phi(p_0)(t)=1, \phi(p_1)(t)=t-1, \phi(p_2)(t)=(t-1)^2, \phi(p_3)(t)=(t-1)^3\}.$$

To find the coordinates of $p(t)=1+t^3$ in the new basis, we look for scalars $a_j$ such that $$ p(t)=a_0+a_1(t-1)+a_2(t-1)^2+a_3(t-1)^3. $$ Changing $t$ for $t+1$, this is equivalent to $$ p(t+1)=a_0+a_1t+a_2t^2+a_3t^3. $$ Now $p(t+1)=1+(t+1)^3=\ldots$? Develop using the binomial theorem.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.